Misterios de un minuto : mas misterios cortos que resuelves con ciencias! = One minute mysteries :more short mysteries you solve with science! - Yoder, Eric; Yoder, Natalie, 1993-; Yoder, Eric.; Yoder, Eric. (Washington, D.C. : Science, Naturally!, 2016)
c
"Excerpted from One minute mysteries : 65 more short mysteries you solve with science!"
Includes index.
Ages 8-12.
Grades 4-8.
Text in English and Spanish.
Keywords: Science -- Methodology -- Juvenile literature; Science -- Miscellanea -- Juvenile literature; Science -- Study and teaching (Middle school) -- Juvenile literature; Detective and mystery stories -- Juvenile literature; Ciencia -- Metodologia -- Literatura juvenil; Ciencia -- Miscelanea -- Literatura juvenil; Ciencia -- Ensenanza (Media) -- Literatura juvenil; Historias misterio y detectives -- Literatura juvenil